2020
DOI: 10.1002/mgg3.1265
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of urogenital malformations in a female fetus with de novo 15q24 microdeletion and a literature review

Abstract: Background15q24 microdeletion is a relatively new syndrome caused by nonallelic homologous recombination (NAHR) between low‐copy repeats (LCRs) in the 15q24 chromosome region. This syndrome is characterized by a spectrum of clinical symptoms including global developmental delay, intellectual disability, facial dysmorphisms, and congenital malformations of the extremities, eye, gastrointestinal tract, genitourinary system, and genitalia.MethodMolecular cytogenetic analysis was performed using whole genome singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Three known syndromes were involved in our study. Among them, 15q24 Microdeletion Syndrome (#613,406) and 8q21.11 Microdeletion Syndrome (#614,230) were rarely characterized by FGR 25 . As for 22q11.21 microdeletion, which is responsible for DiGeorge Syndrome or Velocardiofacial Syndrome, FGR was frequently reported in FGR with structural malformations 12 , 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Three known syndromes were involved in our study. Among them, 15q24 Microdeletion Syndrome (#613,406) and 8q21.11 Microdeletion Syndrome (#614,230) were rarely characterized by FGR 25 . As for 22q11.21 microdeletion, which is responsible for DiGeorge Syndrome or Velocardiofacial Syndrome, FGR was frequently reported in FGR with structural malformations 12 , 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Microdeletion Syndrome (# 614230) were rarely characterized by FGR 24 . As for 22q11.21 microdeletion, which is responsible for DiGeorge Syndrome, FGR was frequently reported in FGR with structural malformations [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Gu et al [ 23 ] demonstrated that mice with a GJA5 allele deletion exhibited a series of congenital heart defects, including PS. Patients with 15q24 microdeletion syndrome are primarily characterized by intrauterine growth delay, short stature, intellectual disability, microcephaly, and congenital heart defects, among other symptoms [ 24 ]. In this study, the prenatal ultrasound phenotypes of one fetus with 15q24 microdeletion syndrome were consistent with such symptoms, consisting not only of PS but also a ventricular septal defect, fetal growth restriction, and nasal bone dysplasia.…”
Section: Discussionmentioning
confidence: 99%